Avaliação das condições higiênico sanitárias de abatedouro de ovinos - Aguiar, João Maurício Ferreira (Universidade Federal Rural do Semi-Árido, 2017)
The majority of commercial slaughterhouses are deficient in the implementation of hygienic-sanitary procedures that seek to guarantee the safety and quality of the product. The objective of this study was to evaluate the hygienic-sanitary conditions of a sheep slaughterhouse, with State Inspection Service (SIE) in the state of Rio Grande do Norte. There were two technical visits to the establishment to fill a questionnaire about the sanitary and structural aspects of the facilities, equipment and employees. Samples of meat coming directly from the slaughter line were collected for the purpose of microbiological analysis (Coliforms at 35 and 45ºC , Staphylococcus aureus, Salmonella spp.). The result of the sample processing revealed negligible levels of contamination, in keeping with the high compliance rate (93.3%) in items evaluated by the checklist. A variation of <3 to 43 NMP / g was observed for coliforms 35 and 45°C, with also the absence of Salmonella spp. in the meat samples that were analyzed. Therefore, it was concluded that the hygienic-sanitary conditions of the slaughter process were sufficient to ensure a positive quality standard for the sheep meat.
Monografia
Keywords: Abate; Ruminantes; Contaminação; Boas práticas de fabricação; Higiene; Slaughter; Ruminants; Contamination; Hygiene; Good manufacturing pratices; CIENCIAS AGRARIAS::MEDICINA VETERINARIA